The contribution of the ABCG2 C421A polymorphism to cancer susceptibility: a meta-analysis of the current literature - Chen Pin; Zhao Lin; Zou Peng; Xu Haitao; Lu Ailin; Zhao Peng (BMC Cancer, 2012)
Abstract Background ABCG2, also known as BCRP, is a half ATP-binding cassette (ABC) transporter that localizes to plasma membranes. Recently, a number of studies have investigated the relationship between the C421A polymorphism in ABCG2 and cancer risk in multiple populations and various types of cancers; however, this relationship remains unclear. Therefore, we performed a meta-analysis to further explore this association. Methods The meta-analysis incorporated 10 studies involving a total of 3593 cases and 5875 controls. Odds ratios (ORs) and 95% confidence intervals (CIs) were calculated based on the date extracted from the studies to evaluate the strength of association. We also analyzed the heterogeneity and sensitivity of each report and the publication bias of the studies. Results Overall, our results showed that there appeared to be a significant association between the ABCG2 C421A polymorphism and decreased cancer susceptibility (heterozygote-AC versus CC: OR = 0.759, 95%CI = 0.620-0.930; dominant effects model-AA/AC versus CC: OR = 0.771, 95%CI = 0.634-0.938; additive effects model-A allele versus C allele: OR = 0.809, 95%CI = 0.687-0.952). Similarly, decreased cancer risk was also found after stratification of the SNP data by cancer type, ethnicity and source of controls in heterozygote model, dominant effects model and additive effects model. Conclusions We found that the ABCG2 C421A polymorphism is a protective factor for developing cancer. The same relationship was found when the studies were stratified by cancer type, ethnicity and source of controls.